Cosmology and Native North American Mystical Traditions - Grim, John (Théologiques)

(untitled) (Faculté de théologie de l'Université de Montréal, 2001)
ABSTRACTDifferent indigenous nations in North America provide examples of mystical participation in the processes of creation. Some observers dismiss native communities as fragmented or romantically reimaged as "ecological Indians", yet, the tenacity of their religious insights deserve attention. Intellectually framed in images of interactions between specific peoples with particular geographical places, these images are also embedded in dynamic performances. This paper presents a comparative study of mystical paths among First Peoples in which personal and communal symbols fuse psychic, somatic, and social energies with local landscapes. Experienced as synesthetic intuitions, these images are made more conscious in rituals. These dynamic performances link words, actions, sounds, sights, and sensory observations. Ritualized expressions of native mystical life are themselves interpretive reflections back upon the personal, communal, spiritual, and ecological realms from which they emerge. Native American religious ways, thus, are lifeway complexes that address the limits and problems of the human condition, and foster mature mystical understanding.